Identification of a new lesch-nyhan syndrome mutation (HPRT BRASIL) and analysis of potentially heterozygous females - PATRICK O'NEILL; LUCY TROMBLEY; MARY GUNDEL; TIMOTHY HUNTER; JANICE A. NICKLAS; MARA LUCIA S. FERREIRA; MARIA JULIA BUGALLO; ANTÔNIO CARLOS FARIAS; ALFREDO LOHR; MERI DIAMANTOPOULOS; SALMO RASKIN (Arquivos de Neuro-Psiquiatria)
The mutation in the hypoxanthine-guanine phosphoribosyltransferase (HPRT) gene has been determined in two brothers affected with Lesch-Nyhan syndrome. Female members of the family who are at risk for being heterozygous carriers of the HPRT mutation were also studied to determine whether they carry the mutation. DNA sequencing revealed that the boys' mother is heterozygous for the mutation in her somatic cells, but that three maternal aunts are not heterozygous. Such carrier information is important for the future pregnancy plans of at-risk females. The mutation, an A-->T transversion at cDNA base 590 (590A-->T), results in an amino acid change of glutamic acid to valine at codon 197, and has not been reported previously in a Lesch-Nyhan syndrome male. This mutation is designated HPRT Brasil.